Creating EM-associations, study their effects on the pasture grasses and biological activity of degraded soils (Experimental biology, 2016)
At the present time, in Kazakhstan there are trend towards to degradation of pastures. This poses the problem of their restoration. The most promising solutions - using EM technology, based on the introduction in soil of EM-association. The aim this study was selection of strains, creation of EM-associations, study of their effect on meadow grass and biological activity of the soils. From the ecologically pasture’s soil of Almaty region the nitrogen-fixing, cellulolytic and phosphatemobilizing bacteria were isolated. Their biocompatibility was studied, nine strains of were selected. From them 84 variants were created. For the selection perspective EM-associations, their effect on meadow grass and soil biological activity was studied. The inoculation of seed with EM-associations increased green biomass of meadow grasses on the 25-30%. The introduction EM-associations in the soil increased activity of the soil’s enzymes (dehydrogenase increased in 6.2-7.0, catalase and urease in 4.5-5.0 times), and soil respiration in 6-7 times as compared with control. On the basis of these EM-associations will be possible to restoration of the degraded pasture soils.
Keywords: degraded soils; pastures; effective microorganisms (EM); EM-association; fertility soils